PERCEPTUAL MAPPING OF SOAP PRODUCT IN PACKAGING DESIGN (CASE STUDY: LIFEBUOY AND LUX BODY WASH) IN MANADO CITY BY USING MULTIDIMENSIONAL SCALING ANALYSIS - Kasenda, Veisy V.F.; Lapian, S. L. H. V. Joyce; Tumbuan, Willem J.F.A (Universitas Sam Ratulangi, 2017)
Abstract: Packaging design is an important part of any marketing plan that involves product- not only is the messaging and visual identity of a package of reflection of consistent branding. Using Perceptual Mapping is the most important part of marketing because Customer perception are relate to how consumer evaluate a company’s product. The right perception will produce the right decision also to achieve sales of a company. The purpose of this study was to determine the mapping of consumer perceptions of two soap products Lifebuoy and Lux body wash, based on four attributes, color, shape, image and typography. Data were obtained from questionnaires, study of literature and some observation directly to the purpose of the research. Analysis using multidimensional scaling techniques, samples taken 122 samples of people in Manado. The results showed that the consumer has its own perception of each product based on attributes of Lifebuoy and Lux body wash. Therefore, producer soap product, to pay more attention for the packaging design, more influence on customer perception. A better package design could lead to customer attraction and increasing sales.Keywords: perceptual mapping, marketing